Pengaruh Kompetensi, Tarif Pelabuhan dan Kualitas Pelayanan Terhadap Loyalitas Melalui Kepuasan Pelanggan sebagai Variabel Intervening pada PT. Covanova Trans Services Batam - Wirawan, Donny; Ngaliman, Ngaliman; Yasa, I Wayan Catra (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research was conducted at PT. Coranova Trans Service Batam aims to 1) find out how competency, port rates and service quality influence customer satisfaction; 2) find out how port tariff competency and service quality influence loyalty through customer satisfaction; 3) find out how competence indirectly influences loyalty through customer satisfaction; 4) find out how port tariffs indirectly influence loyalty through customer satisfaction; 5) find out how service quality indirectly influences loyalty through customer satisfaction. The research method used is quantitative with descriptive research using a questionnaire instrument in the form of a Likert scale. The results of this research found that partially competency, port rates, and service quality have a significant and positive influence on customer satisfaction. Partially, competency, port rates and service quality have a significant and positive influence on customer loyalty. Competence, port rates and service quality have a significant and positive influence on customer loyalty through customer satisfaction at PT. Covanova Trans Services Batam